A Cross-Linguistic Perspective: A Comparative Study of Pronoun Usage in Chinese and Indonesian - Rabbani, Dzun Nun Septin Renda; Ren, Huiling; Churotaayun, Elisa; Putri, Aira Fitya (International Journal of Chinese Interdisciplinary Studies, 2025)
The course paper is about the comparative analysis of pronouns in Chinese and Indonesian. In every language, pronouns are used to refer to people or things. My research method is to explain the types of pronouns in the two languages ​​(Chinese and Indonesian), the usage structure of pronouns in sentences, and then conduct a comparative analysis. From the structure of the comparative analysis, I point out the similarities and differences between Chinese and Indonesian pronouns. In terms of demonstrative pronouns, Chinese has more demonstrative pronouns than Indonesian, and their forms are mostly the same. There are six types of interrogative pronouns in Chinese and Indonesian, but Chinese has more interrogative pronouns than Indonesian.